Sistem Klasifikasi Air Mineral Layak Minum berdasarkan Nilai PH dan Kekeruhan Menggunakan Metode Naive Bayes berbasis Arduino Uno - Faza Gustaf Marrera; Barlian Henryranu Prasetio; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Water is a very important natural resource for the survival of humans, one of which is as a source of consumption. The safety standards for drinking water established by the government are very important to ensure the safety of the drinking water we consume. To be safe for health, drinking water must meet physical, microbiological, chemical, and radioactive requirements. However, there are still some areas in Indonesia that face difficulties in ensuring the safety of the drinking water they consume. From this problem, researchers want to make a drinking water quality detection system that can provide information related to pH and water clarity to users. The drinking water quality detection system is made using the pH-4502C and turbidity SEN0189 sensors and the Arduino UNO microcontroller connected to the 16x2 LCD as an information display. The results of the two sensors will then be classified using the Naive Bayes method. In this study, sensor testing and method testing have been conducted. The results obtained in the pH-4502 accuracy test are 96.54%. Then, based on the results of the SEN0189 turbidity sensor test, it can be seen that the SEN0189 turbidity sensor can work well in reading the condition of water being cloudy or not. From the readings taken on drinking water (clear) and coffee water (cloudy), it can be seen that the voltage values produced by the sensor are different. A higher voltage value indicates that the water is clearer, while a lower voltage value indicates that the water is cloudier. In the Naive Bayes accuracy test, the result obtained is 100% of 15 total test data and 30 training data. The data is in the form of drinking water in a public environment.